Proses Penegakan Hukum Terhadap Pelaku Tindak Pidana Penipuan Dan Atau Penggelapan Berkedok Biro Jasa Ibadah Umroh Dengan Biaya Murah (Studi Kasus Pada Penyidik Sat Reskrim Polrestabes Semarang) - Zaenul Arifin; Sri Endah Wahyuningsih; Sri Kusriyah (Jurnal Hukum Khaira Ummah, 2020)
Fraud against the implementation of Umrah worship in violation of authority and rights, although the government has issued Law Number 13 Year 2015 on Umroh Worship Implementation which has been experiencing approximately 4 years in effect, but there are still many Umrah travel agencies who commit fraud to prospective Umrah pilgrims. The related fraud case in question is about the criminal act of fraud which has the objective element for the victim to be used for umroh fee by using false profession and institution (umroh distributor) guile or set of lies to fool the victim. The purpose of this study is to find out how the law enforcement of police in investigation of criminal acts of fraud of prospective pilgrims umroh, knowing factors inhibiting the police in the investigation of criminal acts of fraud prospective pilgrims umroh and to find a solution about police barriers in the investigation of criminal acts fraud prospective pilgrims umroh at the stage of investigation on investigator Sat Reskrim Polrestabes Semarang. The methodology used is the empirical approach. Adapaun source and type of data in this study is the primary data generated from field studies with 3 investigators at Sat Reskrim Polrestabes Semarang City. And secondary data from literature study. The conclusion of this research is the mention of anti-disaster against the evidence, make a list of people (DPO) and arrest the suspect. In 2017 the investigation conducted is to examine the relationship, check the staff at the ministry of religion of Semarang City.Keywords: Law enforcement, Investigations, Umrah Jamaah Candidate Fraud